Deep Neck Abscess with Concurrent Orbital and Subgaleal Extension Secondary to Odontogenic Infection: A Case Report - Pande Agus Parta Prananda; Putu Dian Ariyanti Putri; I Made Wiranadha; I Dewa Gede Arta Eka Putra; Eka Putra Setiawan; Sari Wulan Dwi Sutanegara (Archives of The Medicine and Case Reports, 2025)
Deep neck infections (DNIs) originating from odontogenic sources are common, but extensive spread involving concurrent orbital and subgaleal spaces is rare. DNIs can lead to life-threatening complications, particularly in patients with comorbidities like diabetes mellitus (DM) and chronic kidney disease (CKD), which impair immune function. This report details a complex case of DNI with unusual superior extension. A 44-year-old male with poorly controlled type 2 DM and CKD presented with a two-day history of rapidly progressing left facial, submandibular, parotid, and orbital swelling, associated with fever, trismus, and severe pain, originating from a carious mandibular molar. CT imaging confirmed an extensive abscess involving the left masticator, submandibular, sublingual, parotid, and parapharyngeal spaces, with contiguous spread to the left preseptal orbital space and the fronto-temporo-parietal subgaleal space. Multidisciplinary management involved urgent surgical drainage of the submandibular and subgaleal abscesses, odontectomy of the offending molar, broad-spectrum intravenous antibiotics (Citrobacter amalonaticus and Proteus hauseri identified on culture), intensive glycemic control, hemodialysis, and supportive care. In conclusion, this case highlights the potential for aggressive craniofacial spread of odontogenic DNIs, particularly in immunocompromised individuals. Concurrent orbital and subgaleal extension represents a rare and serious complication. Prompt diagnosis with imaging, aggressive multidisciplinary surgical and medical management, including addressing underlying comorbidities, were crucial for a successful outcome.